INTERACTION OF CULTURE AND LANGUAGE IN THE PROCESS OF THEIR FUNCTIONING - Israfilova, G.F (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The ideas of cognitive cultural linguistics have a certain historical base, linguistic and cultural studies, which was formed in the second half of the twentieth century in the framework of teaching Russian as a foreign language. By that time, Linguistic and Regional Studies had developed a fairly stable scientific and theoretical base thanks to the key developments of E.M. Vereshchagin, V.G. Kostomarova, Yu.E. Prokhorova, G. D. Tomakhina and others. The linguistic and cultural theory has received recognition of the linguistic community because within the framework of this scientific and methodological direction, there is a relatively stable system of terminological designations and initial principles for the analysis of specific linguistic material. Of course, there is no need to talk about the absolute independence of cultural linguistics as a scientific doctrine. It represents a separate area of general linguistic-cognitive theory, occupying related positions with other areas of cognitive science in general. This can be seen even from the dictionary definition of cultural linguistics as "a scientific discipline that investigates the relationship and interaction of culture and language in the process of their functioning. Linguistic and cultural studies are carried out at the intersection of sociolinguistics, psycholinguistics, ethnolinguistics, cultural linguistics, cultural studies and other related sciences. The formed scientific picture, which historically determined the formation of various directions of the cognitive theory of language and cognitive linguistics, should be supplemented with the latest information from the history of linguistic teachings, which can be useful in terms of answering the attempts of some researchers to link the emergence of cognitive paradigms mainly with the developments of Western (American and German) cognitive scientists. At the same time, it should be noted that in cognitive linguistics there is a general conceptual basis for the specific correlation of language and thinking, which is a way of working with internal cognitive representations.